Penggunaan Akronim "AUM" dalam Komunikasi Pemerintah Kabupaten Tabanan dengan Masyarakat - I Nyoman Surpa Adisastra; Prabawa, Bagus Ade Tegar; Swarthini, Ni Nyoman Ayu; Arinatha, I Dewa Agung Wahyu (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2025)
Religious symbols or terms are often used in political contests in Indonesia, including in Bali. In Tabanan Regency, under the leadership of Regent I Komang Gede Sanjaya and Deputy Regent I Made Edi Wirawan, the vision is articulated as “Nangun Sat Kerthi Loka Bali melalui Pola Pembangunan Semesta Berencana menuju Tabanan Era Baru yang Aman, Unggul, Madani (AUM)”. The use of the acronym “AUM” is particularly interesting, as in Hinduism, the term “AUM” symbolizes the divine power of God with its three manifestations: Brahma, Vishnu, and Shiva. This study aims to: 1) Examine the meaning of the acronym “AUM” in the communication between the Tabanan Regency Government and the community; 2) Identify the impact of using the acronym “AUM” in such communication; and 3) Analyze the social ethics of using “AUM” in Tabanan Regency. This research used Semiotics Theory, Mass Communication Effects Theory, and Social Morality Theory. This research adopts a qualitative descriptive approach, with informants selected through purposive sampling. The findings indicate that the use of the acronym “AUM” in communication carries both political and philosophical significance. It is perceived to have positive impacts. From a social ethics perspective, the use of the acronym “AUM” has not yet received formal criticism, but further socialization is encouraged. In conclusion, the use of the acronym “AUM” by the Tabanan Regency Government is having positive impacts. However, broader socialization is necessary to clarify the distinction between the political aspect of “AUM” as an acronym and “AUM” as a sacred symbol in Hinduism. Keywords: AUM, communication, Hinduism